2009
DOI: 10.1074/jbc.m808974200
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of the GTPase-activating Protein-related Domain from IQGAP1

Abstract: IQGAP1 is a 190-kDa molecular scaffold containing several domains required for interaction with numerous proteins. One domain is homologous to Ras GTPase-activating protein (GAP) domains. However, instead of accelerating hydrolysis of bound GTP on Ras IQGAP1, using its GAP-related domain (GRD) binds to Cdc42 and Rac1 and stabilizes their GTP-bound states. We report here the crystal structure of the isolated IQGAP1 GRD. Despite low sequence conservation, the overall structure of the GRD is very similar to the G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
63
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(74 citation statements)
references
References 46 publications
(54 reference statements)
8
63
0
2
Order By: Relevance
“…The name "IQGAP" originates as a result of this domain organization, but no report has convincingly demonstrated its GAP activity toward any small GTPases, which is in agreement with the finding that the GAP domain of IQGAPs lacks the arginine finger that is critical for GAP activity (Kurella et al, 2009). Subsequent studies revealed IQGAP1 to be an effector of Rac1 and Cdc42, and the GRD domain in IQGAP1 was later shown to stabilize Rac1 and Cdc42 in the GTP-bound active form (Noritake et al, 2005;White et al, 2012).…”
Section: The Iqgap Familysupporting
confidence: 50%
“…The name "IQGAP" originates as a result of this domain organization, but no report has convincingly demonstrated its GAP activity toward any small GTPases, which is in agreement with the finding that the GAP domain of IQGAPs lacks the arginine finger that is critical for GAP activity (Kurella et al, 2009). Subsequent studies revealed IQGAP1 to be an effector of Rac1 and Cdc42, and the GRD domain in IQGAP1 was later shown to stabilize Rac1 and Cdc42 in the GTP-bound active form (Noritake et al, 2005;White et al, 2012).…”
Section: The Iqgap Familysupporting
confidence: 50%
“…The GRD illustrates other unique properties of IQGAPs. Though similar in sequence to GAPs, the IQGAP GRD has an arginine replaced by threonine at a conserved catalytic residue found in GAPs [107]. This is a key feature to bind to and stabilize small G-proteins in their GTP bound form.…”
Section: Iqgaps Regulate Cellular Functionsmentioning
confidence: 99%
“…The surrounding region, 1045-1195, was investigated because it included residues that are also implicated in Cdc42 binding. Thr1046 is needed to inhibit the GTPase [23], whereas Tyr1192 and Arg1194 were predicted to play a role in Cdc42 binding [39]. For the Rac ligand outside the CBD, nine conformations forming multiple H-bonds were predicted.…”
Section: Molecular Dynamics Simulations Of Gtpase Binding On Iqgapmentioning
confidence: 99%
“…Chimera software is developed by the Resource for Biocomputing, Visualization, and Informatics at the University of California, San Francisco. The crystallographic structure of the GAP-related domain of IQGAP1, 3FAY [23], was obtained from the Research Collaboratory for Structural Bioinformatics (RCSB) database at bwww.rcsb.orgN [24]. The target, 3FAY, and ligands were submitted for blind docking using SwissDock software from Swiss Institute of Bioinformatics [25].…”
Section: Molecular Modelingmentioning
confidence: 99%